The influencing factors of elder-friendly public open spaces promoting older adults’ health in deprived urban neighborhoods: Partial Least Square Structural Equation Modeling approach - Lak, Azadeh; Khodakarim, Soheila; Myint, Phyo K.; Baradaran, Hamid R. (Frontiers in Public Health, 2023)
Background Public open spaces (POSs) is considered a feature of the built environment that is important for physical, mental, and social health during life and contributes to active aging. Hence, policymakers, practitioners, and academics have recently focused on indicators of elder-friendly environments, particularly in developing countries. Objective This study aimed to examine the attributes of POSs and socio-demographic status that positively influence older people’s health in Tehran’s deprived neighborhoods using a pathway model. Methods We employed a pathway model to explore the relationships between place function, place preferences, and process in the environment as the perceived (subjective) positive features of POSs associated with older adults’ health, compared to the objective attributes of POSs. We also included personal characteristics, including physical, mental, and social dimensions, to explore how these factors are related to the health of older adults. To assess the subjective perception of POSs attributes, 420 older adults were asked to complete Elder-Friendly Urban Spaces Questionnaire (EFUSQ) from April 2018 to September 2018 in the 10th District of Tehran. We used the SF-12 questionnaire and “The self-Rated Social Health of Iranians Questionnaire to measure older people’s physical and mental health and elder social health.” Geographical Information System (GIS) measures (Street connectivity, Residential density, Land use mix, Housing quality) were derived as objective measures of neighborhood features. Results According to our findings, the personal aspect, socio-demographic status (such as Gender, Marital status, Education, Occupation as well as Frequency of being present in POSs), place preferences (Security, Fear of Falling, Way Finding and Perceived Aesthetics), and process in the environment’s latent (Social Environment, Cultural Environment, Place Attachment, and Life Satisfaction)constructs collectively influenced the elders’ health. Conclusion We found positive associations between Place preference, Process-in-environment, and personal health-related factors to elders’ health (social, mental, and physical). The path model presented in the study could be guided in future research in this area and inform the development of evidence-based urban planning and design interventions for improve older adults health and social functioning and quality of life.